Diagnostics of banana blood disease - Rincón-Flórez, Vivian A.; Ray, Jane D.; Carvalhais, Lilia C.; O’Dwyer, Cecilia A.; Siti Subandiyah; Zulperi, Dzarifah; Drenth, André (The American Phytopathological Society (APS), 2022)
Blood disease in bananas caused by Ralstonia syzygii subsp. celebesensis is a bacterial wilt disease that causes major yield losses of banana in Indonesia and peninsular Malaysia. The disease has significantly increased its geographic distribution in the past decade. Diagnostic methods are an important component of disease management in vegetatively propagated crops such as banana to constrain incursions of plant pathogens. Therefore, the objectives of this study were (i) to design and rigorously validate a novel banana Blood disease (BBD) real-time PCR assay with a high level of specificity and sensitivity of detection and (ii) to validate published PCR-based diagnostic methods targeting the intergenic region in the megaplasmid (“121 assay” with primer set 121) or the phage tail protein-coding sequence in the bacterial chromosome (“Kubota assay” and “BDB2400 assay” with primer set BDB2400). Assay validation included 339 samples (174 Blood disease bacteria, 51 bacteria associated with banana plants, 51 members of the Ralstonia solanacearum species complex, and 63 samples from symptomatic and healthy plant material). Validation parameters were analytical specificity (inclusivity and exclusivity), selectivity, limit of detection, accuracy, and ruggedness. The 121 assay and our newly developed BBD real-time PCR assay detected all R. syzygii subsp. celebesensis strains with no cross-specificity during validation. Two different PCR assays using the primer set BDB2400 lacked specificity and selectivity. This study reveals that our novel BBD real-time PCR assay and the conventional PCR 121 assay are reliable methods for Blood disease diagnostics, as they comply with all tested validation parameters.